Simultaneous measurement of twenty-nine circulating cytokines and growth factors in female patients with overt autoimmune thyroid diseases - Chao-Wen Cheng; Chung-Ze Wu; Kam-Tsun Tang; Wen-Fang Fang; Jiunn-Diann Lin (Taylor & Francis Group, 2020)
Cytokines and growth factors participate in immune responses, and the pathogenesis of autoimmune diseases. Herein, we simultaneously examined differential levels of 29 circulating factors to determine their associations in female patients with overt autoimmune thyroid disease (AITD). We enrolled 40 patients with Graves' disease (GD), 20 patients with Hashimoto's thyroiditis (HT), and 14 healthy controls. Twenty-nine circulating factors were simultaneously measured. GD patients with low thyroid-stimulating hormone at the time of sample collection were defined as having active GD. B-cell activating factor (BAFF) levels were associated with GD and HT (p = .001 and .001, respectively) and interferon (IFN)-α levels were higher in the HT group than in the control group (p = .021). Significant associations of serum BAFF and tumour necrosis factor (TNF)-α levels with free thyroxin (FT4) were present in HT (r = −0.498, p = .026, and r = 0.544, p = .013, respectively). Meanwhile, there were significant associations of FT4 with interleukin (IL)-4 and eotaxin levels in GD (r = 0.354, p = .025 and r = 0.384, p = .014, respectively). In active GD, serum BAFF and eotaxin level were correlated with FT4 levels (r = 0.465, p = .034, and r = 0.463, p = .035, respectively). In conclusion, BAFF is the best circulating indicator to identify GD and HT among all chosen 29 biomarkers, and it could be used to predict the disease severity in HT and active GD. Meanwhile, IFN-α could be another reliable parameter for recognising HT.